Peningkatan Kompetensi Guru dalam Identifikasi dan Asesmen Anak Berkebutuhan Khusus di Sekolah Inklusif - Nabilah Putri Awaliah; Ayunda Khoirunisa; Rani Anjelina; Hendri Marhadi (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
Inclusive education is very important in this era of globalization, where it is hoped that all children, including children with special needs (ABK), have the same right to receive education. This research aims to understand teachers' abilities in recognizing ABK and effective strategies for assessing their abilities, as well as helping facilitate learning that suits the needs and abilities of ABK. This research uses a literature review approach by analyzing various literature sources, articles and related research that have been published previously. The research results show that there are many strategies that have been used to improve teachers' abilities in recognizing and assessing students with special needs in inclusive schools. This strategy includes training and workshops, preparation of an inclusive curriculum, mentoring by experts, and the use of educational technology. The results of this research also show that these approaches can improve teachers' professional abilities, support learning tailored to the needs of students with special needs, and reduce exclusion in the educational context. Therefore, it is hoped that these strategies can become a reference in improving the quality of inclusive education in inclusive schools.